PERBANDINGAN MODEL ALTMAN Z-SCORE, SPRINGATE DAN ZMIJEWSKI DALAM MEMPREDIKSI KEBANGKRUTAN INDUSTRI TEKSTIL DI BEI - Nita Afifah; Damayanti Damayanti (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
The Textile and Textile Products (TPT) industry is one of the strategic sectors in the Indonesian economy. However, in recant years it has faced considerable pressure due to the COVID-19 pandemic, global economis slowdown, and increasing import competition. These conditions have led to a decline in finanicial performance and an increased risk of bankruptcy among textile companies. Therefore, reliable bankruptcy prediction result among the Altman Z-Score, Springate S-Score dan Zmijewski X-Score models, as  well as to determine the most accurate model in predicting bankruptcy of textile industry companies listed on the Indonesia Stock Exchange during the 2020 – 2024 period. The research sample was selected using a purposive sampling method, resulting in 15 textile companies as research samples. Hypothesis testing in this study was conducted using the Kruskal-Wallis test. The Result indicate that there are significant differences among the Altman Z-Score, Springate S-Score dan Zmijewski X-Score models in predicting bankruptcy. Furthermore, the Zmijweski model is found to be the most accurate in predicting bankruptcy in the textile industry, with an accuracy rate of 70,67%. This study is limited to the use of three bankruptcy prediction models.